The Influence of Smart Technologies Adoption in Enhancing the Port Efficiency: A Case of Dar Es Salaam Seaport, Tanzania - Chaula , William (AGUSPATI Research Institute, 2025)
Smart technologies have revolutionized port operations making the port activities and processes more efficient. This study examined the influence of smart technology adoption on enhancing operational efficiency at the Dar es Salaam seaport, Tanzania's largest and busiest port. The research was guided by three specific objectives corresponding with smart technology selected components including system automation, real-time data integration, and cybersecurity on port efficiency. The study adopted positivism philosophy and deductive research approach with a descriptive design employed in entire process of methodology. The study collected data from a sample of 95 respondents drawn randomly from port management, shipping companies, and shipping agents. Data collection instruments included structured questionnaires and documentary reviews. Analysis was carried out through descriptive statistics and multiple regressions by using SPSS software. The results of descriptive statistics show that the aggregate average mean of all three variables lie in “agree level” of the liker scale indication that respondents agreed that adoption of smart technology through system automation, real-time data integration, and cybersecurity contributed to port efficiency. Findings of the study demonstrated that system automation had significant enhancement to port efficiency, with a strong positive correlation, indicating that increased automation leads to better operational outcomes. Real-time data integration showed a positive but statistically weaker impact on port efficiency, suggesting benefits that are present but less pronounced. Cybersecurity also demonstrated a significant positive effect on port efficiency, suggesting that increased usage of cybersecurity technology leads to better improved operational outcomes. The study concludes that smart technologies, especially automation and cybersecurity, play critical roles in improving the efficiency of Dar es Salaam seaport operations. The study recommends the port management to continue investing in these smart technologies in parallel with efforts to strengthen real-time data systems for optimal port efficiency. These findings may contribute valuable insights to the port authorities and the government focusing to leverage technology to enhance port operational efficiency.